Delinquent Behavior, Poor Relationship Quality With Parents, and Involvement With Deviant Peers in Delinquent and Nondelinquent Adolescents: Different Processes, Informant Bias, or Both?. (September 2014) - Asscher, Jessica J.; Wissink, Inge B.; Deković, Maja; Prinzie, Peter; Stams, Geert Jan J. M.
The aim of this study was to determine whether two risk factors that are frequently selected as targets for prevention and intervention purposes—involvement with deviant peers and parent–adolescent relationship quality—are associated with delinquent behavior in the same way in a juvenile general population sample ( n = 88) as in a juvenile offender sample ( n = 85). Information on delinquency and the quality of parent–adolescent relationship was obtained from adolescents and parents. The results of path analyses showed that relations between poor parent–adolescent relationship quality, involvement with deviant peers, and delinquency depended on whose point of view is used (adolescent or parent) and which sample is used (general population or delinquent sample). These findings indicate that caution is warranted when theories based on research with community samples are used for development of intervention programs for juvenile delinquents.